The Effect Of Audit Opinion, Audit Quality And Financial Performance On Company Value In The Transportation And Logistics Sector In 2020-2023 - M. Agustiawan Saputra; Yuniarwati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
A company's financial performance, audit opinion, and audit quality can all provide information about its state. The fairness status of a financial report can reveal the audit opinion, competent auditors can gauge the audit quality, and fundamental analysis can reveal the financial performance. This study's goal is to determine how the organization's worth is impacted by audit quality, audit opinion, and financial performance. Participants in this study were logistics and transportation companies that were listed on the Indonesia Stock Exchange between 2020 and 2023. One technique for choosing research samples is purposeful sampling. Twenty-seven companies have fulfilled the criteria for the study sample. The study employs a descriptive method to analyze secondary data and multiple linear regression testing with conventional assumptions, t-test, and f-test. The findings indicate that, between 2020 and 2023, the value of transportation and logistics companies listed on the Indonesia Stock Exchange is significantly impacted negatively by the DAR, but favorably by audit opinions, ROA, and TATO